Pendampingan Pembuatan Alat Permainan Edukatif Berbasis STEAM dan Loose Parts Pada Guru di TK Mancasan Sukoharjo - Fitriyah, Qonitah Faizatul; Rahman, Farid; Fatmarizka, Tiara; Susilo, Taufik Eko; Cahyadi, Mukhlis; Lazuardy, Arzhuma Arza (Jurusan Ilmu Pendidikan - Universitas Lampung, 2023)
STEAM and Loose Parts-based educational game tools are learning media that can stimulate children to have a 21st century mindset and skills. However, the reality shows that teachers at Mancasan Kindergarten still need activities to improve their skills in implementing STEAM and Loose Parts media. Activities are carried out in the form of provision and assistance. Provision takes the form of delivering material that introduces STEAM-based educational game tools and Loose Parts. Next, participants distributed the creation of the educational game tools and then presented it. The work results were in the form of STEAM Based educational game tools and Loose Parts and were awarded. Through this assistance, Mancasan Kindergarten teachers have the knowledge and skills to create an APE.